Combined structural and functional imaging reveals cortical deactivations in grapheme-color synaesthesia - O'Hanlon, Erik; Newell, Fiona N.; Mitchell, Kevin (Frontiers in Psychology, 2013)
Synaesthesia is a heritable condition in which particular stimuli generate specific and consistent sensory percepts or associations in another modality or processing stream. Functional neuroimaging studies have identified potential correlates of these experiences, including, in some but not all cases, the hyperactivation of visuotemporal areas and of parietal areas thought to be involved in perceptual binding. Structural studies have identified a similarly variable spectrum of differences between synaesthetes and controls. However, it remains unclear the extent to which these neural correlates reflect the synaesthetic experience itself or additional phenotypes associated with the condition. Here, we acquired both structural and functional neuroimaging data comparing thirteen grapheme-colour synaesthetes with eleven non-synaesthetes. Using voxel-based morphometry and diffusion tensor imaging, we identify a number of clusters of increased volume of grey matter, of white matter or of increased fractional anisotropy in synaesthetes versus controls. To assess the possible involvement of these areas in the synaesthetic experience, we used nine areas of increased grey matter volume as regions of interest in an fMRI experiment that characterised the contrast in response to stimuli which induced synaesthesia (i.e. letters) versus those which did not (non-meaningful symbols). Two of these areas, in left lateral occipital cortex and in postcentral gyrus, showed sensitivity to this contrast in synaesthetes but not controls. Unexpectedly, in both regions, the letter stimuli produced a strong negative BOLD signal in synaesthetes. An additional whole-brain fMRI analysis identified fourteen areas, three of which were driven mainly by a negative BOLD response to letters in synaesthetes. Our findings suggest that cortical deactivations may be involved in the conscious experience of internally generated synaesthetic percepts